2008
DOI: 10.1074/jbc.m706666200
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Macroautophagy Promotes or Prevents Fibroblast Apoptosis Depending on the Death Stimulus

Abstract: Macroautophagy has been implicated as a mechanism of cell death. However, the relationship between this degradative pathway and cell death is unclear as macroautophagy has been shown recently to protect against apoptosis. To better define the interplay between these two critical cellular processes, we determined whether inhibition of macroautophagy could have both pro-apoptotic and anti-apoptotic effects in the same cell. Embryonic fibroblasts from mice with a knock-out of the essential macroautophagy gene atg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
94
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 68 publications
4
94
0
Order By: Relevance
“…3,15 In studies using mammalian cells in culture which were exposed to various ER stress-inducing drugs or polyglutamine aggregates, autophagy was alternatively described as either death protective or death promoting. 4,14,30,31 It has been proposed that autophagy contributes to cell death in nontransformed cells, while it serves to attenuate apoptotic cell death in transformed cancer cell lines. 4 Here, we found that the ER-induced autophagy in primary fibroblasts had prodeath characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…3,15 In studies using mammalian cells in culture which were exposed to various ER stress-inducing drugs or polyglutamine aggregates, autophagy was alternatively described as either death protective or death promoting. 4,14,30,31 It has been proposed that autophagy contributes to cell death in nontransformed cells, while it serves to attenuate apoptotic cell death in transformed cancer cell lines. 4 Here, we found that the ER-induced autophagy in primary fibroblasts had prodeath characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, genetic knockdown of Atg5 was shown to sensitize hepatocytes to cell killing following exposure to menadione, associated with ATP depletion and activation of the c-Jun-NH 2 -terminal kinase ( JNK) pathway (181), whereas Atg5 -/ -embryo fibroblasts resisted menadione-induced apoptosis (161,180). The explanation for variable results observed between experimental models is not entirely clear but may include cell-type and inducer-specific effects, dosedependent effects, off-target activities of autophagy proteins and inhibitor compounds, and differential availability of compensatory mechanisms.…”
Section: Autophagy In Oxidative Cellular Stressmentioning
confidence: 99%
“…69 Although early evidence suggested that autophagy is a form of cell death, more recent investigations support a predominant if not exclusive function for autophagy as a pro-survival pathway. 70,71 The metabolism of lipids by lipophagy suggests several new mechanisms by which autophagy may act to prevent cell death. Potential cellprotective effects of lipophagy include the breakdown of lipids to supply energy to maintain cell function and prevent ATP depletion that leads to necrosis or apoptosis from mitochondrial dysfunction and the ability to promote the metabolism of potentially toxic lipid molecules (Figure 3).…”
Section: Lipophagy Mediates Resistance To Cell Deathmentioning
confidence: 99%